Coverage of the European Parliament Elections of 1999: National Public Spheres and European Debates - Kevin, Deirdre (Javnost-The Public, 2001)
This article is based on the results of an eight-country study on national media coverage of European political and cultural affairs, which included the final week of the European Parliament election campaigns. The research was carried out during two monitoring periods in 1999 with the co-operation of partner institutes in France, Germany, Ireland, Italy, the Netherlands, Spain, Sweden and the United Kingdom. Coverage of the campaigns in each country provided an opportunity to examine media debates during a political event at a level above the nation-state. The coding of news items and articles allowed for a quantitative assessment of news coverage and frequency of reference to particular topics, while a qualitative overview of coverage by national experts facilitated the comparison of national debates. While the elections represent a process of political participation outside the national sphere, there is no corresponding common sphere of debate, which can be examined in relation to this exercise of citizenship. Comparing the activity in the various national spheres highlighted some of the distinct national ideas and debates about European Union membership while also bringing to the fore some common concerns and debates which reflect growing political and economic integration.